2023
DOI: 10.3389/fphar.2023.1223742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on gut microbiota and short-chain fatty acids in patients with functional constipation: a randomized placebo-controlled trial

Xiang-Yun Yan,
Jun-Peng Yao,
Yan-Qiu Li
et al.

Abstract: Objective: To comprehensively evaluate the effect of acupuncture on gut microbiota, identify specific microbes closely related to the clinical efficacy of acupuncture, and explored the role of short-chain fatty acids (SCFAs).Methods: A randomized placebo-controlled trial was conducted with 80 FC patients and 28 healthy controls (HCs). FC patients randomly received 16 acupuncture (n = 40) or sham acupuncture (n = 40) sessions over 4 weeks; HCs received no treatment. The change in the proportion of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Additionally, acupuncture, a traditional practice with a history of over 3000 years in China and some other Asian countries, has been recognized by the WHO as a recommended treatment for constipation, recent studies have reported that acupuncture at acupoints Tianshu (ST25), Shangjuxu (ST37), and Fujie (SP14) is safe and effective in treating constipation. Acupuncture has regulatory effects on gastrointestinal motility and gastric acid secretion, while also influencing gastrointestinal cells, hormones, and neurotransmitters in the intestinal nervous system [13]. This leads to improved gastrointestinal function and alleviation of constipation symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, acupuncture, a traditional practice with a history of over 3000 years in China and some other Asian countries, has been recognized by the WHO as a recommended treatment for constipation, recent studies have reported that acupuncture at acupoints Tianshu (ST25), Shangjuxu (ST37), and Fujie (SP14) is safe and effective in treating constipation. Acupuncture has regulatory effects on gastrointestinal motility and gastric acid secretion, while also influencing gastrointestinal cells, hormones, and neurotransmitters in the intestinal nervous system [13]. This leads to improved gastrointestinal function and alleviation of constipation symptoms.…”
Section: Introductionmentioning
confidence: 99%